Exploring the Relationship between Colonial Education and Nationalism in Indonesia: A Reading of Pramoedya A. Toer’s This Earth of Mankind - FX Dono Sunardi; Pratiwi Retnaningdyah; Slamet Setiawan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: The research investigates the relationship between participation in colonial education and the emergence of nationalism in Indonesia. To better understand this relationship, it mainly analyzes the main character's portrayal of Pramoedya A. Toer's novel, This Earth of Mankind (1990). Method: The study uses a literary analytical approach to explore and interpret the main character's experiences and reactions within the colonial educational system as depicted in the novel. Results: The research concludes that merely undergoing colonial education does not directly lead to the rise of nationalism in Indonesia. Instead, individuals' complex and subjective experiences within this system, particularly navigating identity amidst challenges, foster nationalist sentiments. The protagonist's journey, as depicted in the novel, showcases how these subjective experiences contribute to developing nationalist feelings. Novelty: A distinctive aspect of the study is its emphasis on subjectivity, highlighting how individuals can autonomously and uniquely respond to challenging situations. The research also offers a nuanced perspective on the influence of colonial education on the growth of nationalism in Indonesia, addressing gaps in existing literature and building upon Viswanathan's (1989) inquiry into the mechanisms through which colonial education impacts nationalist sentiments.